SOCIO-PEDAGOGICAL FEATURES OF FORMATION OF MOTIVATION IN NON-PHYLOLOGICAL HIGHER EDUCATIONAL ESTABLISHMENTS (Scientific journal of the Fergana State University, 2023)
The article discusses the issue of motivation, which is an important factor in teaching foreign languages ​​in non-philological universities, and also emphasizes the need to take into account the students’ needs, capabilities and abilities to increase motivation.